Comparative environmental footprints of lettuce supplied by hydroponic controlled-environment agriculture and field-based supply chains. (1st October 2022) - Casey, Leanne; Freeman, Ben; Francis, Kurt; Brychkova, Galina; McKeown, Peter; Spillane, Charles; Bezrukov, Andrey; Zaworotko, Michael; Styles, David
Abstract: Attributional life cycle assessment was applied to determine environmental footprints of lettuce produced across ten supply chain configurations, based on either hydroponic closed-environment agriculture (CEA) with six different electricity sources, or field supply chains involving regional, continental or inter-continental transport. Hydroponic CEA systems use circa 15 kWh of electricity for lighting, cooling, ventilation and pumping per kg of lettuce supplied. Based on typical current national grid electricity generation mixes with significant fossil fuel dependence, this results in large environmental footprints, e.g. up to 17.8 kg CO2 eq. and 33 g N eq. per kg lettuce – compared with 10 kg CO2 eq. and 16 g N eq. per kg lettuce air-freighted across continents. However, hydroponic CEA can produce orders of magnitude more produce per m 2 .yr and can be integrated into existing buildings (e.g. on roof tops, in basements and disused warehouses, etc). Factoring in the carbon opportunity costs of land use, and meeting electricity requirements exclusively through renewable generation, could result in closed hydroponic CEA delivering produce with a smaller carbon footprint than most field-based supply chains, at 0.48 kg CO2 eq. per kg lettuce. However, this would only be the case where renewable electricity originates from genuinely additional capacity, and where a land use policy or other mechanisms ensure that modest areas of land spared from horticultural production are used for "nature based solutions" such as afforestation. Hydroponic CEA uses orders of magnitude less direct water than field-based systems, and could help to mitigate water stress and associated soil degradation in arid and semi-arid regions used for horticulture – so long as upstream water stress associated with electricity generation is mitigated. CEA could be one of the least sustainable forms of food production if poorly implemented, and has numerous environmental hotspots. But with careful design and scaling, in appropriate contexts of high demand and low agro-climatic potential for production of horticultural produce, CEA deployment could play a role in sustainable food system transformation, potentially helping to reconnect consumers with (urban) producers. There may be opportunities to link building air handling systems with rooftop or basement CEA requiring inputs of cooling, CO2 and water. Highlights: Hydroponic closed environment agriculture (CEA) benchmarked against conventional supply chains Large environmental footprints for CEA lettuce when powered by mixed grid electricity Relatively small environmental footprints for CEA lettuce when renewable electricity used Land and water use efficiency 38–60 times higher for CEA than open-field lettuce production Carefully designed CEA systems could contribute to sustainable supply of fresh produce